DNA barcoding of Mugilogobius mertoni and M. rambaiae from Siberut and Enggano Islands, the small outermost islands of Sumatra, Indonesia - DEWI IMELDA ROESMA; DJONG HON TJONG; SYAIFULLAH SYAIFULLAH; DYTA RABBANI AIDIL (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Roesma DI, Tjong DH, Syaifullah, Aidil DR. 2025. DNA barcoding of Mugilogobius mertoni and M. rambaiae from Siberut and Enggano Islands, the small outermost islands of Sumatra, Indonesia. Biodiversitas 26: 386-395. Siberut and Enggano Islands are the small and outermost islands of Sumatra, Indonesia. These two islands' unique geological history allows evolutionary processes to produce high levels of endemicity. One of the interesting fish genera from the Siberut and Enggano Islands is Mugilogobius. Based on morphological identification, it was estimated there are two Mugilogobius species in the Siberut and Enggano Islands. Molecular identification of Mugilogobius using the Cytochrome Oxidase I gene (known as DNA barcoding) needs to be done to prove it. The liver tissue was used for molecular analysis. The BLAST analysis showed that Mugilogobius from Siberut and Enggano Islands have a similarity range of 97.49%-96.06% with Mugilogobius GenBank. Based on the 558 bp sequence analyzed, Mugilogobius mertoni and Mugilogobius rambaiae from Siberut and Enggano Islands have a low sequence of divergences at 0.0%-0.4%, respectively. M. rambaiae from Siberut and Enggano Islands share the same haplotype. The ability of the species to maintain their genetics and the similarity of conditions between the two islands share their high genetic similarities. M. mertoni and M. rambaiae from Siberut and Enggano Islands have a high sequence of divergences at 3.0-4.6% with M. mertoni and M. rambaiae GenBank, respectively. The long-distance location, the presence of the ocean as a barrier, and differences in habitat conditions contribute to the high variations between Mugilogobius from two islands and other populations. Mugilogobius from Siberut and Enggano Islands has a sequence of divergence at 12.4%-17.3% compared to other Mugilogobius species, supporting their differences at the species level in the same genera. This study contributed to presenting the first molecular data of Mugiologius that can be used as a sequence reference for identification and the sequences became the genetic richness data of fish in the small and outermost islands of Sumatra, Indonesia (Siberut and Enggano Islands).